Selective removal of anionic dyes using poly(N, N-dimethyl amino ethylmethacrylate) functionalized graphene oxide. Issue 71 (14th July 2016) - Li, Chengpeng; Zhu, Haijin; She, Xiaodong; Wang, Tao; She, Fenghua; Kong, Lingxue
Abstract : An in situ polymerization strategy was used to functionalize graphene oxide (GO) with poly( N, N -dimethyl amino ethylmethacrylate) (PDMAEMA) for the selective removal of anionic dyes. Abstract : An in situ polymerization strategy was used to functionalize graphene oxide (GO) with poly( N, N -dimethyl amino ethylmethacrylate) (PDMAEMA) for the selective removal of anionic dyes. Various characterization methods demonstrate that PDMAEMA-grafted GO (GO-PDMAEMA) was successfully synthesized, and the high PDMAEMA content of 68.5% in GO-PDMAEMA changed the zeta potential significantly from −36.5 (GO) to 41.5 (GO-PDMAEMA). This change in the charge of GO-PDMAEMA greatly increased the adsorption capacities for anionic dye orange G (OG) compared to the pristine GO. The maximum adsorption capacity for anionic OG dye based on the Langmuir model is 609.8 mg g −1 . The adsorption mechanism is believed to be a consecutive process of intra-particle diffusion and surface adsorption, with electrostatic interactions as the key driving force. The GO-PDMAEMA nanocomposite also showed excellent regeneration capacity and selectivity towards the separation of various anionic dyes ( i.e. OG, Eosin yellow and Congo red) from an aqueous dye mixture. In conclusion, our method offers a promising strategy for developing new anionic dye adsorbents.